Lung Abscess: Diagnosis and Treatment - Sherly Lawrensia (Cermin Dunia Kedokteran, 2021)
Lung abscess is a microbial infection of the lungs that results in pulmonary parenchyma necrosis. Meticulous history taking, physical examination, and prompt diagnostic workup are necessary for establishing the diagnosis. Antibiotics are the cornerstone for lung abscess’ treatment with size less than 6 cm.Abses paru adalah infeksi mikroba pada paru yang menyebabkan nekrosis parenkim paru. Anamnesis dan pemeriksaan fisik yang teliti, serta pemeriksaan penunjang yang tepat penting untuk diagnosis. Antibiotik merupakan pilihan terapi utama untuk abses paru berukuran kurang dari 6 cm.